Phosphor Alloyed CrMnNi Austenitic As‐cast Stainless Steel with TRIP/TWIP Effect. Issue 3 (24th July 2013) - Jahn, Andreas; Steinhoff, Karl‐Philipp; Dubberstein, Tobias; Franke, Peter; Weider, Marco; Wolf, Steffen; Kovalev, Alexander; Glage, Alexander; Weiß, Andreas; Schärfl, Wolfgang; Eigenfeld, Klaus; Krüger, Lutz; et al.
Abstract In the present work the influence of phosphor on the flowability, the effect on the infiltration of ZrO2 open foam ceramics and the martensite formation as well as the resulting mechanical properties of high alloyed CrMnNi as‐cast steels is studied. Additionally, the effect of phosphor on surface tension is investigated. The study is performed using thermodynamic calculations, static tensile tests, notch‐bar impact tests, optical light microscopy, scanning electron microscopy, energy dispersive X‐ray analysis, electron backscatter diffraction, and the magnetic scale for the detection of ferromagnetic phase fractions. Maximum bubble pressure method is used to measure the surface tension of the liquid steel. The martensite phase fraction is not significantly influenced with increasing phosphor content. The flowability and the quality of the infiltration of open foam ceramics are improved with increasing phosphor contents. The investigated specimens show an increasing yield and an ultimate tensile strength with higher phosphor contents. The uniform and the fracture elongation as well as the notch impact resistance remain at high values. Moreover, an increase in phosphor content did not significantly change the surface tension of the investigated CrMnNi alloys.